Taxonomy of fungus gnats allied to Neoempheria ferruginea (Brunetti, 1912) (Diptera: Mycetophilidae), with descriptions of 11 new species from Japan and adjacent areas - Sueyoshi, Masahiro (Zootaxa, 2014)
Specimens of Neoempheria previously considered to be N. ferruginea (Brunetti, 1912) are studied and revised. Eleven new species are described from Japan, Nepal, Philippines, and Thailand; N. biceltisuta sp. n., N. bifurcata sp. n., N. bisecuriata sp. n., N. brevispathulata sp. n., N. carinata sp. n., N. cuneata sp. n., N. dilatata sp. n., N. denticulata sp. n., N. forficulata sp. n., N. latisternata sp. n., and N. muticata sp. n. Neoempheria sakhalinensis Zaitzev, 2001, is recorded from Japan for the first time. Male genitalia of these 12 species are illustrated. A key to the species is provided. A lectotype of Mycomya ferruginea Brunetti, 1912 is designated (deposited in the Zoological Survey of India, Kolkata) and the species redescribed. Morphological similarities and differences among N. ferruginea and allied species are discussed. The usefulness of the male gonocoxite and associated structures, and the gonapophysis of the female 8th and 9th abdominal sternites for taxonomy are discussed.